EFFECTIVENESS OF STRUCTURED-WORKSHEET USE TO REDUCE STUDENT MISCONCEPTIONS IN STOICHIOMETRY - Irma Ayu Virtayanti; Rosyidah Syafaatur Rohmah (Jurnal Tadris Kimiya, 2020)
This study aims to describe the effectiveness of Structured Problem-oriented worksheets (Structured Worksheet) in reducing misconceptions of 2th Senior High School Lamongan students in the 2019/2020 Academic Year. This study involved 19 students from 2th Senior High School Lamongan. The effectiveness measured by three indicators consist of: the level of mastery learning of students after Learning Activity Using Structured Worksheet; reduction of students' misconceptions; and student response questionnaire. Data obtained from learning outcome tests were included in the learning outcomes analysis format. Diagnostic test data were analyzed using descriptive statistics to find out what percentage of students experience misconceptions. Student response data in the form of satisfaction and motivation questionnaires were analyzed descriptively. The results showed that the average level of student learning completeness was 93 and was above the Standard Minimum Score of 80. The percentage of concept errors experienced by students on stoichiometry material decreased to 98%. Based on the questionnaire given, 89.5% of students have high satisfaction with stoichiometry learning using Structured Worksheet. As much as 78.9% of students have a high level of learning motivation. Based on the results, applying a Structured Worksheet in learning effectively reduces students' misconceptions in stoichiometry.